2018
DOI: 10.1088/1361-6439/aaabf7
|View full text |Cite
|
Sign up to set email alerts
|

Spring constant measurement using a MEMS force and displacement sensor utilizing paralleled piezoresistive cantilevers

Abstract: This paper reports on a method to measure a spring constant on site using a micro electro mechanical systems (MEMS) force and displacement sensor. The proposed sensor consists of a force-sensing cantilever and a displacement-sensing cantilever. Each cantilever is composed of two beams with a piezoresistor on the sidewall for measuring the in-plane lateral directional force and displacement. The force resolution and displacement resolution of the fabricated sensor were less than 0.8 µN and 0.1 µm, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…From the results of the calibration to analyze the relationship between the applied force and the displacement of the cantilever tip, it is confirmed that the cantilever tip stiffness (3,950 N/m) in the lateral direction is approximately five times larger than the cantilever tip stiffness (710 N/m) in the vertical direction. The stiffness of the cantilever tip can be calculated using Equation (1) [29,30]:S=f N/d m where S is the stiffness of the cantilever tip, and d and f are the displacement and force generated in the vertical and lateral directions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…From the results of the calibration to analyze the relationship between the applied force and the displacement of the cantilever tip, it is confirmed that the cantilever tip stiffness (3,950 N/m) in the lateral direction is approximately five times larger than the cantilever tip stiffness (710 N/m) in the vertical direction. The stiffness of the cantilever tip can be calculated using Equation (1) [29,30]:S=f N/d m where S is the stiffness of the cantilever tip, and d and f are the displacement and force generated in the vertical and lateral directions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…MEMS spring is a typical microstructure, which not only provides elastic force but also transmits energy [4][5]. It is a key component of many micro-sensors [6] and actuators [7][8], and its performance determines the accuracy, output linearity of the device. Some researchers have tried to apply and measure the micro force with MEMS springs as driving sources.…”
Section: Introductionmentioning
confidence: 99%